Temporal discounting and problematic technology use: a scoping review - Fonseca, Samuel de Araujo; Oliveira-Castro, Jorge M. (Perspectivas em Análise do Comportamento, 2025)
This study conducted a scoping review to investigate the relationship between problematic technology use (such as the internet, video games, smartphones, and social media) and temporal discounting, which reflects the preference for immediate rewards over delayed ones. Using the PRISMA-ScR protocol, articles from seven databases (PubMed, PsycInfo, Scopus, among others) were analyzed, following steps of identification, selection, eligibility, and inclusion. The search combined terms such as “Delay discounting AND Problematic Technology Use”, with criteria that included correlational or experimental studies published between 2010 and 2024, peer-reviewed, and written in Portuguese, English, or Spanish. Fifty articles that indicated a positive relationship between excessive technology use and high rates of temporal discounting were included. The theoretical bases included behavioral economics (e.g., reinforcement pathology theory) and behavior analysis (e.g., Behavioral Perspective Model). Temporal discounting was assessed with reinforcers such as money, screen time, and likes, measured by standardized or adapted instruments. Problematic use was associated with consumption of the Internet, social media, games, and music, assessed directly (screen time) or indirectly (self-report). The study contributes to understanding how excessive technology use can affect decision-making.